2021
DOI: 10.3390/su13158386
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Start-Up Business Model—Qualitative Analysis

Abstract: The aim of the research is an in-depth and detailed knowledge of the start-up business model, which is structured according to Canvas visualization. The research sample contains 106 start-ups operating in Slovakia. Each start-up was researched by a member of the research team, who personally recorded the statements of the founder. The research results are based on qualitative analysis and synthesis of statements of the founders of start-ups. The main results of the research are a summary view of the business m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Pivoting is a well-documented phenomenon in startup ecosystems. Bandera and Thomas (2019) note that slightly over one-fifth of all U.S. startups in the Kauffman Firm Survey underwent at least one pivot, a finding echoed by Slávik, Bednár and Mišúnová Hudáková (2021), who observed that a quarter of Slovakian startups significantly altered or developed their business concept. VCs uniquely contribute by recognizing the entrepreneur's value-creation potential and understanding why the initial research effort did not succeed and what aspects can be repurposed.…”
Section: Introductionmentioning
confidence: 95%
“…Pivoting is a well-documented phenomenon in startup ecosystems. Bandera and Thomas (2019) note that slightly over one-fifth of all U.S. startups in the Kauffman Firm Survey underwent at least one pivot, a finding echoed by Slávik, Bednár and Mišúnová Hudáková (2021), who observed that a quarter of Slovakian startups significantly altered or developed their business concept. VCs uniquely contribute by recognizing the entrepreneur's value-creation potential and understanding why the initial research effort did not succeed and what aspects can be repurposed.…”
Section: Introductionmentioning
confidence: 95%
“…One of the obstacles in this partner rental business is the negative stigma of society which equates this business with the prostitution business so that business people from Sewapacarbdgg must be able to think innovatively in dealing with these problems. According to Slávik et al, (2021) The criteria for the sustainability of a business are its performance indicators, for example, number of users, number of customers, sales and profits. determining factors that influence performance, for example the quality of staff, the quality of business ideas, the structure of the business model, the choice of company development strategy and the choice of business strategy.…”
Section: E Think Unique and Innovativementioning
confidence: 99%
“…The startup has paramount importance in improving environments and society, which involves critical business activity for existence and growth (Silva et al, 2021). Lean startups and business models in startups are burning topics in entrepreneurship literature (Ghezzi, 2019;Kountur et al, 2020;Lizarelli et al, 2022) (Slávik et al, 2021).…”
Section: Startup Sustainability Based On Government Technology and Ma...mentioning
confidence: 99%